Inactivation of Stachybotrys chartarum grown on gypsum board using aerosolized chemical agents. Issue 1 (2nd January 2006) - Green, Christopher F; Barth, Edward; Scarpino, Pasquale V; Wagner, Andrew; Davidson, Craig; Gibbs, Shawn G; Hoffman, Melissa
Abstract : Aerosolized disinfectant use has appealing qualities for inactivation and remediation of biologically contaminated materials. Their ability to reach exterior and interior spaces of walls and difficult to access areas has potential as a simple and cost effective remediation technique. Stachybotrys chartarum was used as a test organism against four disinfectants: chlorine dioxide, sodium hypochlorite, thiabendazole, and cupric sulfate - sodium hydroxide solution. Tests were conducted independently. The organism was exposed for 4 and 8 h periods to the aerosolized disinfectant. The building material was commercially available gypsum board with paper facing. This material was inoculated under sterile conditions. The commercially available treatments were administered as aerosols generated from a collison nebulizer directed into a sterile growth chamber housing inoculated gypsum board. Surface samples were collected before and after exposures to determine treatment effects. The aerosolized chlorine dioxide and sodium hypochlorite treatments successfully inactivated the organism after 8 h of continuous exposure.